Recovery from respiratory failure after 49-day extracorporeal membrane oxygenation support in a critically ill patient with COVID-19: case report. Issue 1 (12th December 2020) - Guo, Fengwei; Deng, Chao; Shi, Tao; Yan, Yang
Abstract: Background: Respiratory failure is a life-threatening complication of coronavirus disease 2019 (COVID-19)-related acute respiratory distress syndrome. Extracorporeal membrane oxygenation (ECMO) in COVID-19 might offer promise based on our clinical experience. However, few critically ill cases with COVID-19 have been weaned off ECMO. Case summary: A 66-year-old Chinese woman presented with fever (38.9°C), cough, dyspnoea, and headache. She had lymphopenia (0.72 × 10 9 /L) and computed tomography findings of ground-glass opacities. Subsequently, she was confirmed to have respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. She was intubated after transfer to the intensive care unit due to respiratory failure and heart failure. However, her condition continued to deteriorate rapidly. Veno-veno ECMO was undertaken for respiratory and cardiac support due to refractory hypoxemic respiratory failure and bradyarrhythmia (45 b.p.m.). During hospitalization, she was also administered anti-viral treatment, convalescent plasma therapy, and continuous renal replacement therapy. She was maintained on ECMO before she had fully recovered from the condition that necessitated ECMO use and had a negative test for the nucleic acids of SARS-CoV-2 twice. Forty-nine days later, this patient was weaned from ECMO. At the most recent follow-up visit (3 months after weaning from ECMO), she received respiratory and cardiac rehabilitation and did not complain of any discomfort. Discussion: As far as we know, the longest duration of ECMO treatment in this critical case with COVID-19 is supportive of ECMO as the most aggressive form of life support and the last line of defence during the COVID-19 epidemic.